Peningkatan Pemahaman Mahasiswa Tentang Labeling Negatif melalui Bimbingan Kelompok Berbasis Al-Qur’an - Zhila Jannati (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
Negative labeling on children can have a negative impact on children. Children will feel isolated, sad, disappointed, and can even make negative behavior worse. The purpose of this study was to find out how to increase students' understanding of negative labeling through Al-Qur'an-based group guidance. The method used in this research is qualitative method. The data collection techniques are observation and interview techniques. The subjects of this study were 10 students of the Islamic Guidance and Extension Study Program, Raden Fatah State Islamic University Palembang. Data analysis in this study used descriptive qualitative data analysis. The results of this study are: (1) The implementation of Al-Qur'an-based group guidance through four stages, namely the formation stage, the transition stage, the activity stage (core), and the termination stage, and (2) Students' understanding of negative labeling has improved both in aspects of (a) an understanding of the meaning of negative labeling, (b) an understanding of the causes of negative labeling, (c) an understanding of the various types of labeling, (d) an understanding of the impact of negative labeling on individuals, and (e) an understanding of how to prevent negative labeling behavior towards others.